THE IN VITRO ANTIOXIDANT PROPERTIES OF 2-ALKOXYPHENYLCARBAMIC ACID DERIVATIVES CONTAINING A 4´-(SUBSTITUTED PHENYL)PIPERAZIN-1´-YL MOIETY DETERMINED BY THE 2,2´-AZINOBIS(3-ETHYLBENZOTHIAZOLINE-6-SULFONIC ACID) DERIVED RADICAL CATION (ABTS•+) AND FERRIC RE - Ivan Malík; Lukáš Stanzel; Jozef Csöllei; Jana Čurillová (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
In an effort to comprehensively characterize an antioxidant profile of 2-alkoxyphenylcarbamic acid-based compounds containing a 4´-(substituted phenyl)piperazin-1´-yl fragment, they were in vitro screened in the 2,2´-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) derived radical cation (ABTS•+) and ferric reducing antioxidant power (FRAP) assay using the UV/VIS spectrophotometry. The ABTS•+ scavenging (reducing) potential of 1-[3-(2-methoxyphenylcarbamoyl)oxy-2-hydroxypropyl]-4-(4-fluorophenyl)piperazin-1-ium chloride was found to be the most promising and it was comparable to the efficiency of the carvedilol reference drug. Moreover, that 4´-fluoro group-containing compound was regarded as more active than the atenolol standard. When testing the molecules´ power to reduce the ferric 2,4,6-tris (2-pyridyl)-s-triazine complex [Fe(III)(TPTZ)2]3+, the most prospective was 1-[3-(2-ethoxyphenylcarbamoyl)oxy-2-hydroxypropyl]-4-(4-fluorophenyl)piperazin-1-ium chloride. On the other hand, its Fe3+ reducing power was lower compared to both standards carvedilol and atenolol. The study discussed structure–antioxidant properties relationships considering electronic, steric and lipophilic features.